(untitled) (The Review of Diabetic Studies, 2025)
Background and aim: Substance use during pregnancy and the postpartum period is a critical public health concern with serious repercussions for both mothers and their infants. Despite increased awareness, maternal substance use remains a pervasive challenge in obstetric care. This study aims to assess the correlation between maternal opioid and other substance use—including Medication-Assisted Treatment (MAT) status and toxicology—and subsequent neonatal outcomes. Material and methods: This prospective, observational, and interdisciplinary cohort study tracked pregnant women with substance use disorders and their neonates from initial presentation through delivery and NICU care. The maternal cohort included women aged 18 and older, while the neonatal cohort comprised their infants. Exclusion criteria included significant medical or psychological disorders unrelated to substance use. Results: The study examined the demographic and obstetric profiles of 25 mothers. The mean maternal age was 29.64 years, and the majority (64%) were married. Oral administration was the primary route of substance use (52%). Key symptoms included drowsiness and poor coordination (68%), with 44% of the cohort experiencing significant opioid-related complications. Urine toxicology confirmed a 40% prevalence of opiate positivity. Regarding neonatal outcomes, the mean birth weight was 2.95 kg with a mean gestational age of 37.7 weeks. Signs of Neonatal Abstinence Syndrome (NAS) were prevalent; 44% of newborns required pharmacological intervention, predominantly with morphine. Conclusion This study underscores the interplay between maternal education, substance use patterns, and delivery outcomes. The findings suggest that despite significant variability in use, optimized neonatal and maternal outcomes may be achieved through rigorous prenatal care and comprehensive clinical oversight.